Measurement of W±-boson and [Zeta]-boson production cross-sections in pp collisions at √s=2.76 TeV with the ATLAS detector - Aaboud, Morad; Andrei, George Victor; Bolz, Arthur; Dunford, Monica; Franchino, Silvia; Kugel, Andreas; Napolitano, Fabrizio; Schöning, André; Schultz-Coulon, Hans-Christian; Spieker, Thomas; Stamen, Rainer; Starovoitov, Pavel; et al. (The European physical journal. C, Particles and fields, 2019)
The production cross-sections for W± and Z bosons are measured using ATLAS data corresponding to an integrated luminosity of 4.0 pb(-1) collected at a centre-of-mass energy √s=2.76 TeV. The decay channels W → lv and Z → ll are used, where l can be an electron or a muon. The cross-sections are presented for a fiducial region defined by the detector acceptance and are also extrapolated to the full phase space for the total inclusive production cross-section. The combined (average) total inclusive cross-sections for the electron and muon channels are: s tot W+ → lv = 2312 ± 26 (stat.) ± 27 (syst.) ± 72 (lumi.) ± 30 (extr.) pb, s tot W- → lv = 1399 ± 21 (stat.) ± 17 (syst.) ± 43 (lumi.) ± 21 (extr.) pb, s tot Z → ll = 323.4 ± 9.8 (stat.) ± 5.0 (syst.) ± 10.0 (lumi.) ± 5.5(extr.) pb. Measured ratios and asymmetries constructed using these cross-sections are also presented. These observables benefit from full or partial cancellation of many systematic uncertainties that are correlated between the different measurements.
Im Titel sind das Plus- und das Minuszeichen hochgestellt
Im Titel ist "Zeta" als griechischer Buchstabe dargestellt
Im Titel steht der Buchstabe s unter dem Wurzelsymbol
ATLAS Collaboration*: George Victor Andrei, Arthur Bolz, Monica Dunford, Silivia Franchino, Andreas Kugel, Fabrizio Napolitano, André Schöning, Hans-Christian Schultz-Coulon, Thomas Spieker, Rainer Stamen, Pavel Starovoitov, Sebastian Weber, Martin Wessels, Xiaoguang Yue [und 2905 weitere]
Gesehen am 05.06.2020